2020
DOI: 10.1016/j.isci.2019.100765
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Hemorrhagic Shock Syndrome-on-a-Chip

Abstract: Ebola virus, for which we lack effective countermeasures, causes hemorrhagic fever in humans, with significant case fatality rates. Lack of experimental human models for Ebola hemorrhagic fever is a major obstacle that hinders the development of treatment strategies. Here, we model the Ebola hemorrhagic syndrome in a microvessel-on-a-chip system and demonstrate its applicability to drug studies. Luminal infusion of Ebola virus-like particles leads to albumin leakage from the engineered vessels. The process is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 70 publications
0
52
0
Order By: Relevance
“…The most complete documentation illustrating the efficacy of melatonin to thwart Ebola virulence is the recent detailed study of Junaid et al (71). This group specifically tested melatonin against Ebola-mediated hemorrhagic shock, which is the most prominent and deadly feature of an infection of this type.…”
Section: Fig 1 Effects Of Melatonin On Ebola Virus Induced Hemorrhamentioning
confidence: 99%
See 2 more Smart Citations
“…The most complete documentation illustrating the efficacy of melatonin to thwart Ebola virulence is the recent detailed study of Junaid et al (71). This group specifically tested melatonin against Ebola-mediated hemorrhagic shock, which is the most prominent and deadly feature of an infection of this type.…”
Section: Fig 1 Effects Of Melatonin On Ebola Virus Induced Hemorrhamentioning
confidence: 99%
“…Junaid and coworkers initially grew microvessels using human endothelial cells (HUVECs) adjacent to a collagen type I network (71). To ensure the endothelial cells exhibited the physiological barrier function of in vivo capillaries, the authors examined the potential transport of albumin through the endothelial wall into the collagen matrix and found no albumin leaked from the experimental vessel.…”
Section: Fig 1 Effects Of Melatonin On Ebola Virus Induced Hemorrhamentioning
confidence: 99%
See 1 more Smart Citation
“…The morphological change strongly indicates the possibility of impaired endothelial barrier function after reduction of SEMA3F expression. To test this postulation we assessed the effect of SEMA3F KD on endothelial barrier function through the use of electric cell-substrate impedance sensing (ECIS) [13] and the more physiological 3D-endothelial tube in a microfluidics platform [14]. With each method we found that, targeted reduction of SEMA3F in ECs resulted in impaired barrier function ( Figure 6A Next, we assessed whether loss of barrier function upon SEMA3F knock down alters monocyte transendothelial migration with monocyte chemotaxis over Transwell filters containing endothelial monolayers with SEMA3F knock down or control cells.…”
Section: Loss Of Sema3f Impairs Endothelial Barrier Functionmentioning
confidence: 99%
“…Melatonin is a naturally occurring molecule assumed to be present in every species [ 19 ]. Due to its antioxidant, anti-inflammatory, as well as other properties [ 20 , 21 , 22 , 23 , 24 , 25 ], it has been speculated to be a promising molecule for treating COVID-19 patients [ 18 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], and also other deadly viral infectious diseases [ 48 , 49 , 50 , 51 ]. A small scale clinical trial has also shown promising results [ 52 ].…”
Section: Introductionmentioning
confidence: 99%